Comparing efficacy of fibrates and statins in isolated and combined hypertriglyceridemia and various types of oxidative metabolism - G. S. Mal’ (Кардиоваскулярная терапия и профилактика)
Aim. To compare efficacy of simvastatin, a II generation statin, and ciprofibrate, a III generation fibrate, in various types of hyperlipidemia (HLP) and fibrate pharmacokinetic variants. Material and methods. The authors examined 156 males with primary HLP, aged 41-59. Inclusion criteria were: initial cholesterol (CH) >190 mg/dl; triglycerides (TG) >150 mg/dl; high-density lipoprotein CH >35 mg/dl. Clinical, biochemical, pharmacokinetic, and statistical methods were used. Results. Analysis of lipid-transport system in patients with isolated hypertriglyceridemia (HTG) during 8-week ciprofibrate therapy demonstrated decreases in TG (by 39.2%; pIII-V<0.05), and atherogenicity index, AI (by 28.6%; pIII-V<0.05). In patients with HTG and hypercholesterolemia (HCH), CH level was significantly reduced (by 13.1%; pIII-V<0.05), mostly due to 33.1% decrease in low-density lipoprotein CH (pIII-V<0.001). Analysis of the association between ciprofibrate-induced TG decrease and oxidative parameters demonstrated greater numbers of the patients with inadequate hypotriglyceridemic effect among “fast” oxidative metabolisers than among “slow” ones. Among individuals with “fast” oxidation phenotype, ciprofibrate therapy had a moderate hypotriglyceridemic effect in 67% of subjects (p<0.05). Conclusion. In combined HTG and HCH, substantial hypotriglyceridemic activity of ciprofibrate was observed among patients with “slow” oxidation phenotype: TG concentration decreased by 35% (р<0.001). In “fast” oxidation phenotype group, TG level was reduced by 30% (р<0.05). Participants with both isolated and combined HTG demonstrated a substantial hypolipidemic effect of ciprofibrate in “slow” oxidation phenotype.